An Investigation of Canine Hepatic Dysfunction Using Different Diagnostic Methods - Verma, P.; Arora, N.; Kalita, J. C.; Singh, A. K.; Prasad, A.; Mrigesh, M. (International Journal of Bio-resource and Stress Management, 2024)
The present investigation was executed at Department of Veterinary Medicine and Dr. I. P. Singh Veterinary Clinical Complex and Trauma Centre, College of Veterinary and Animal Sciences, G.B.P.U.A. & T, Pantnagar U.S. Nagar, Uttarakhand, India during the period of September, 2021 to April, 2022. The present study aimed to diagnose hepatic dysfunction in dogs presented to Dr. I.P. Singh Veterinary Clinical Complex and Trauma Centre, Pantnagar. Eighteen dogs presented with varied symptoms of hepatic dysfunction such as fever, anorexia, vomition, emaciation, polydipsia, polyuria, dullness, diarrhoea, icterus and nervous signs indicating hepatic affections were selected irrespective of their age breed, sex and were subjected to haematological, biochemical, radiographic and ultrasonographic examination. Alterations in hematobiochemical parameters of dogs with hepatic dysfunction were compared with healthy dogs. Findings of haematological examination revealed significant decrease in Hb, PCV, TEC, platelets, lymphocytes whereas there was significant increase in neutrophils in dogs with hepatic dysfunction as compared to healthy dogs. Findings of biochemical parameter revealed significant increase in total bilirubin ALT, AST, GGT, ALP whereas there was significant decrease in total protein, albumin, A:G ratio, blood glucose of dogs with hepatic dysfunction as compared to healthy dogs. Radiography and ultrasonography were found useful in diagnosis of canine hepatic dysfunction. Ultrasonography offers additional advantages over radiography by allowing for the evaluation of echogenicity, echotexture, size, shape, and margins of the liver. From the study it was concluded that combination of diagnostic test is reliable to diagnose hepatic dysfunction in dogs and single diagnostic test can be misleading.